A Future Prospect on the Adoption of Augmented Reality E-Commerce in Malaysia - Wahab, Eta; Ronaldo, Niel (Research in Management of Technology and Business, 2022)
Technological advancements and developments are growing at a fast pace these days. However, there are lack of study that look at the AR e commerce especially from the perspective of consumer adoption. Thus, this study will focus on the foresight study on the adoption of AR e-commerce in Malaysia. There will be two research objectives in this research which is to identify the key drivers of Augmented Reality (AR) e-commerce adoption among online consumers in Malaysia and to determine the future trend of Augmented Reality (AR) e-commerce adoption among online consumers in Malaysia. The research had been conducted among Malaysian consumers; the research had collected 110 responses from respondent with a response rate of 28.95%. This study found that motivates consumers purchasing decisions and consumer data protection and privacy as the highest driver in impact-uncertainty analysis. Four (4) scenarios have been proposed at the end of the study. The four scenarios are stagnant state of AR technology, flourish of AR technology in e-commerce, incapable of AR technology, and destructibility of AR technology.